Inflammation and Neurotransmission of the Vescico-Uterine Space in Cesarean Sections. (January 2013) - Malvasi, A.; Dell'Edera, D.; Cavallotti, C.; Creanza, A.; Pacella, E.; Di Renzo, G.C.; Mynbaev, O.A.; Tinelli, A.
Collagen IV and laminin play a key role in regulating stiffness, elasticity and flexibility of the vescico-uterine space (VUS) tissue. The neurotensin (NT), the neuropeptide tyrosine (NPY) and the protein gene product 9.5 (PGP 9.5) possessing vasorelaxation and tissue vascularization activities, play key roles in cervical ripening, scar innervations and pain control. We propose that the integrity of these substances in VUS tissue is compromised after Cesarean section (CS), since wound healing disturbances and pelvic pain, as well as pregnancy and delivery complications, are related with lower uterine segment dysfunctions after CS. Therefore, the contents of collagen IV, laminin, NT, NPY and PGP 9.5 nerve fibres from the VUS tissue samples obtained during the first CS and the repeated CS were comparatively studied. VUS specimens were collected from 104 patients during CS and evaluated by immunohistochemistry. Collagen IV and laminin were mostly found in the vascular membrane bounds and their images were quantitatively evaluated by Quantimet Leica analyzer software. Differences of collagen IV, laminin, NT, NPY and PGP 9.5 values in VUS tissue between the first CS and the repeat CS samples were calculated by Student's Mest. Reduced laminin and increased collagen IV values were observed in the VUS scar tissue after the repeated CS in comparison with those of VUS intact tissue obtained during the first CS. Significantly higher values of nerve fibres, containing NT, NPY and PGP 9.5 were registered in intact VUS tissue samples, respectively 5±0.7, 7±0.6 and 5±0.9 CU, than those of VUS scar tissue samples obtained during the repeated CS, respectively 3±0.6, 2±0.4 and 3±0.7 CU (p<0.05). The authors observed increased collagen IV and reduced laminin values after the repeated CS which might be the key signs of inflammatory damage of VUS scar tissue by CS. These findings were strengthened by the registration of decreased NT, NPY and PGP 9.5 values in the same samples, which are important neurotransmitters and are responsible for optimal wound healing, pain control and lower uterine segment functions.